New Approaches to the Governance of Natural Resources
XXVIII, 292 p.
Keywords: The book provides an in-depth analysis of the governance of Africa's natural resource sectors (oil, biofuels, forestry, fisheries, minerals) and new insights for readers as they navigate the burgeoning research on global governance initiatives and regional/national strategies that seek to improve the governance of the continent's natural resources.